Validation of a method for in situ determination of 137Cs soil contamination density in kitchen gardens using the portable spectrometer-dosimeter MKS AT6101D - V. P. Ramzaev; A. N. Barkovsky; A. A. Bratilova (Радиационная гигиена)
The collection of representative soil samples in the territory of settlements and subsequent measurements of the content of radionuclides in these samples under laboratory conditions (the so-called “ex situ method”) is a generally accepted technology for determining the density of soil contamination with 137Cs in the populated areas contaminated due to the Chernobyl accident. Recently, as a supplement or alternative to the ex situ method, researchers are developing field (in situ) gamma-spectrometry methods. These methods allow determining the density of soil contamination with 137Cs directly on site, without soil sampling and laboratory analysis. At the same time, the in situ methodology has several limitations, the most important of which is a lack of generally recognized metrological basis for measurements and interpretation of results. Hence, before using a particular technique and measuring device for carrying out large-scale in situ measurements, it is necessary to validate (to assess the suitability) of the selected in situ method using an established ex situ method. The aim of this study was to validate the method for determining the density of 137Cs soil contamination in kitchen gardens using the MKS AT6101D spectrometer-dosimeter in situ. The method was recently presented by a Russian-Swedish-Belarusian group of researchers in an article published in the Journal of Environmental Radioactivity (https://doi.org/10.1016/j.jenvrad.2021.106562). To validate this method, we selected 10 representative kitchen garden plots. The plots were located in six settlements of the Bryansk region in Russia. The territory of the settlements had been heavily contaminated with 137Cs as a result of the Chernobyl accident: the officially established levels of the density of soil contamination by 137Cs ranged from 111 to 511 kBq/m2 in 2017. Field gamma-ray spectra were recorded at a height of 1 m above the ground in the center of kitchen garden plots using the MKS AT6101D device. The measurement duration was in the range of 1207–1801 s (the mean value = 1383 s). Samples of soil in the kitchen gardens were taken layer by layer (with a step of 5 cm) to a depth of 20 cm using a demountable cylindrical sampler. The 137Cs content in each soil layer was determined in the laboratory using a stationary semiconductor gamma spectrometer. The values of the 137Cs contamination density of the sampled soils ranged from 77 to 548 kBq/m2. It was found that the results of the ex situ analyzes of soil samples were in a good agreement with the contamination density values obtained with the in situ method. On average, the difference between two methodologies was 7% (a maximum of 20%). The results of the study confirm that the method proposed by the international group is suitable for determining the density of soil contamination by 137Cs in kitchen gardens in remote period after the Chernobyl accident.